A fresh look at IBS—opportunities for systems medicine approaches. Issue 3 (7th November 2016) - Albusoda, A.; Barki, N.; Herregods, T.; Kamphuis, J. B. J.; Karunaratne, T. B.; Lazarou, M.; Lee, I.; Mazurak, N.; Perna, E.; Polster, A.; Pribic, T.; Uhlig, F.; et al.
Abstract: NeuroGUT is a EU‐funded initial training network (ITN) of 14 research projects in neurogastroenterology that have employed an equal number of early‐stage researchers. Neurogut trainees have—among other activities—attended an international conference on irritable bowel syndrome (IBS) in Bologna in 2016 and were asked to critically review and evaluate the current knowledge on IBS for their respective research activities, and to state what they were missing. Most appreciated were the topics brain imaging of gut activity, the role of the gut microbiota, the pharmacology of gut functions, the IBS‐IBD interrelation, the new Rome IV criteria, the role of gas, and the placebo response in functional disorders. Missed were more detailed coverage of high‐resolution manometry, functional brain imaging, advanced "systems medicine" approaches and bioinformatics technology, better sub‐classification of IBS patients, and the development of disease biomarkers, extended at the molecular (genetic/epigenetic, proteonomic) level. They summarize that despite excellent specialized research, there is a gap open that should be filled with systems medicine. For this, it would be necessary that medical research learns even more from the data sciences and other basic disciplines, for example, information technology and system biology, and also welcomes a change in paradigm that enhances open sharing of data, information, and resources. Abstract : NeuroGUT is a EU‐funded initial training network (ITN) in neurogastroenterology. Neurogut trainees have attended an international conference on irritable bowel syndrome (IBS) in Bologna in 2016 and critically evaluated the current knowledge on IBS for their respective research activities. They summarize that there is a gap open that should be filled with systems medicine.